Mitigation strategies for supply chain risks in cassava chip SME using house of risk method (A case study in Langgeng Jaya Abadi SME, Malang Regency) - Siti A. Mustaniroh; Dewi A. Ndadari; Dhita M. Ikasari (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2018)
Langgeng Jaya Abadi is a small- and medium-scale entreprise (SME) located in Malang Regency with main business entity of producing cassava chips. In the operational of the business activities, the SME faced various issues that need to be immediately tackled or maintained by implementing risk mitigation strategies. Problems occured in Langgeng Jaya Abadi SME include a time-delay in delivery of cassava, planning mistakes, poor quality of cassava chips, and the sales fluctuation in cassava flour and and cassava chip. This study aimed to identify risk, as well as to assess and determine the risk mitigation strategies. The method used in the research was house of risk (HOR). The variables studied include supply risk, internal risk and demand risk. Four expert respondent were employed composed of supplier, SME owner, SME employee, and distribution agent. The results indicated that there were 24 risk events and 26 risk agents were identified. Risk assessment demonstrated that 2 priority risk agents include SME’s employee negligence and planning errors. The study further determined six mitigation strategies such as evaluating employee performance, providing reprimands and sanctions, scheduling activities, improving demand information on cassava chips, establishing inventory controls, and improving internal coordination systems.